A Multi Criteria Decision Making Methodology Based on Pythagorean Fuzzy Sets for Risk Assessment in Health Sector - (:unkn) unknown (OLD CITY PUBLISHING INC, 2020)
The present paper focuses on the comparison of the Interval-Valued Pythagorean Fuzzy Technique for Order of Preference by Similarity to Ideal Solution (IVPFTOPSIS) and VlseKriterijumska Optimizcija I Kaompromisno Resenje (VIKOR) to resolve uncertainties in risk assessment (RA) in the health sector. The ranking of the different hospital units according to the RA can be similar to solving multiple criteria decision-making (MCDM) problems. In this paper, AHP-TOPSIS based approach was used during the MCDM RA methodology with IVPF sets. Then it was tested using the VIKOR method to validate the results obtained and the proposed model. Weights of risk parameters were calculated using the IVPFAHP method. The risk priority of each unit of the hospital was calculated using the IVPFTOPSIS and these results are crosschecked with VIKOR method; thus, both methods were compared while overcoming uncertainty and achieving optimal results in the RA process. Public places and dining areas were determined as the highest risk by both methods. Moreover, visualization centers, polyclinics, and laboratories were identified as other risky areas by TOPSIS and VIKOR. These units need to be taken seriously and systematically controlled.
Keywords: Risk assessment; occupational health and safety; TOPSIS; VIKOR; MCDM; OCCUPATIONAL-HEALTH; EXTENSION; SAFETY; TOPSIS